The Limits of Leadership as a Barrier to Quality Assurance in Higher Education in Algeria - Belimane Wissam; Chahed Amina (Economics and Business)
Since 2010, Quality Assurance (QA) has been officially adopted and has become a priority of the Higher Education (HE) system in Algeria. This study is part of this framework and aims to explore the role of leadership in the QA process as perceived by Quality Management Managers (QMRs). It is based on a qualitative approach through interviews with 27 QMRs from different institutions. Content analysis technique was used to analyse data.